La question de la tolérance en Occident et en islam à travers le livre de Yves-Charles Zarka et Cynthia Fleury : Difficile tolérance - Makram Abbès (Astérion, 2005)
Yves-Charles Zarka and Cynthia Fleury’s Difficile tolérance seeks to study the question of tolerance within Western societies, and the position occupied by Arab Muslim communities within those societies. The authors stress the incompatibility of Western and Islamic values ; they argue that it is impossible for tolerance to develop within Islamic culture, and assert the need to react against communitarian claims, which they see as increasingly dangerous for the institutions of the French Republic. In this article, the main postulates, assumptions and historical examples put forward by Y. Zarka and C. Fleury are subjected to analysis and critique. The article points out the misreadings, errors of interpretation and distortions on which the two authors rely as they set out their hypothesis of the absence of tolerance within Islamic culture.